Teaching versus facilitating learning - Muralidharan, Etayankara (My University, 2017)
Explore the challenges of teaching business management to undergraduate students aspiring to become managers in the corporate world. The presentation will broadly revolve around enumerating the differences in being just a teacher from being someone facilitating learning among students. Drawing on my two decades of experience in the corporate world (in an international context from a developing country) and contrasting academic experience from my PhD days (in a developed country), I wish to discuss insights (from my experiences being an operating manager and an academic researcher), that I call the ARC framework, and that I believe has been very helpful in my tenure as someone facilitating learning at MacEwan.
Presented October 12, 2017 at the CALIBER Business Teaching Skills Symposium held at MacEwan University in Edmonton, AB.
Keywords: higher education; teaching; learning; undergraduate students